2015
DOI: 10.1007/s11771-015-2779-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pyrite surface state by DFT and AFM

Abstract: The surface states of pyrite (FeS 2 ) were theoretically investigated using first principle calculation based on the density functional theory (DFT). The results indicate that both the (200) and (311) surfaces of pyrite undergo significant surface atom relaxation after geometry optimization, which results in a considerable distortion of the surface region. In the normal direction, i.e., perpendicular to the surface, S atoms in the first surface layer move outward from the bulk, while Fe atoms move toward the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…At the same time, a significant decrease in the peak intensities at 162 and 163 eV and an increase in the peak intensities at 168 and 169 eV were observed in the S (2p) spectrum. This was consistent with the previous study [ 55 ]: the change of S (2p) promoted the regeneration of Fe (Ⅱ) by S as an electron source on the MPy surface, but under acidic conditions, S atoms in the MPy more easily reacted with O atoms in water to form sulfates, which existed in the MPy or were dissolved in solution [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 92%
“…At the same time, a significant decrease in the peak intensities at 162 and 163 eV and an increase in the peak intensities at 168 and 169 eV were observed in the S (2p) spectrum. This was consistent with the previous study [ 55 ]: the change of S (2p) promoted the regeneration of Fe (Ⅱ) by S as an electron source on the MPy surface, but under acidic conditions, S atoms in the MPy more easily reacted with O atoms in water to form sulfates, which existed in the MPy or were dissolved in solution [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 92%
“…Combining inductively coupled plasma atomic emission spectrometry (ICP-AES) and energy-dispersive X-ray analysis (EDS) analysis showed the pyrite contained: 44.984% of Fe, 52.111% of S, 1.287% of SiO 2 , 0.27% of Al, 0.24% of Ca, 0.09% of Ti, and 0.018% of Co. The X-ray diffraction spectrum (XRD) (Figure 1a) indicated that the pyrite sample was absolutely pure compared with the previous work [39]. Some pretreatment of pyrite samples was applied before carrying out the adsorption experiments.…”
Section: Methodsmentioning
confidence: 72%
“…However, these peaks showed a considerable reduction in height, implying the decrease of crystallite size (58.9 nm), which was in consist with Diao et al 25 A higher decrease in (200) and (311) surfaces of nano-pyrite was observed, these two surfaces were found to be S-rich surfaces among the fresh surfaces exposed during crush and grind processes. 26 The S atoms tend to catch O atom from water molecular, and sulfate was released as oxidized products under acidic atmosphere. 27 With the continuous loss of S atom, the (200) and (311) planes, as S-rich sites, therefore showed severe erosion than other planes of nano-pyrite.…”
Section: Characterization Of Pyrite Nanoparticlesmentioning
confidence: 99%